Developing and Piloting a Pedagogy for Teaching Innovation, Collaboration, and Co-Creation in Secondary Education Based on Design Thinking, Digital Transformation, and Entrepreneurship - Athanassios Androutsos; Vasiliki Brinia (MDPI AG, 2019)
In Secondary Education, students need innovative skills and competences that the current education system does not sufficiently offer. Also, educators need pedagogical support to develop teaching to respond to 21st century skills requirements. In order to achieve these goals, an experimental culture of learning needs to be implemented in practice. The aim of this paper is to introduce and pilot a pedagogy for teaching innovation, collaboration, and co-creation in secondary education. The proposed pedagogy is based on a designerly way of thinking, digital competences, and entrepreneurial spirit, together with an experimental culture of creating, making, and collaborating in order to improve students’ innovative, co-creative and collaborative way of thinking and making. The main finding is that the proposed pedagogy enhanced innovative, collaborative and co-creative student competences. Moreover, digital and entrepreneurial skills gave the ability to the students to create new valuable products and services.